2021
DOI: 10.1111/tid.13592
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of central nervous system invasive aspergillosis in a liver transplant recipient using microbial cell‐free next generation DNA sequencing

Abstract: Invasive aspergillosis (IA) is in an important opportunistic infection affecting transplant patients. 1,2 While all solid organ transplant recipients are at risk for invasive aspergillosis, liver transplant patients appear to be at particularly high risk for disseminated disease and have poor outcomes, with mortality ranging from 64% to 100%. 1,3 For liver transplant recipients, time to onset of IA after transplant is decreased when compared to other organ transplant recipients. 1,3,4 Additionally, liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In theory, KT may have greater impact in these patients given the broader differential of infectious pathogens and lower sensitivity of conventional diagnostics to detect them. This finding appears consistent with Rossoff et al who found that KT testing netted a higher yield of clinically relevant pathogens in immunocompromised patients (61%) than in immunocompetent patients (35%) [ 10 ] as well as prior reports of utility in diagnosing mold infections in immunocompromised patients and opportunistic infections in HIV patients [ 3 , 6 , 12 – 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…In theory, KT may have greater impact in these patients given the broader differential of infectious pathogens and lower sensitivity of conventional diagnostics to detect them. This finding appears consistent with Rossoff et al who found that KT testing netted a higher yield of clinically relevant pathogens in immunocompromised patients (61%) than in immunocompetent patients (35%) [ 10 ] as well as prior reports of utility in diagnosing mold infections in immunocompromised patients and opportunistic infections in HIV patients [ 3 , 6 , 12 – 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, publications were searched using specific fungal names and after manual examination five extra articles were added. Therefore, in total 52 articles were included in this review [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Laboratory Diagnosis Of Fungal Infections By Ngsmentioning
confidence: 99%
“…It was a case of allergic bronchopulmonary mycosis where A. fumigatus and Schizophyllum commune sequences were detected in the homogenised sputum and mucoid plugs of the patient [ 26 ]. Since then, up to the time of writing, a total of 319 cases of fungal infections diagnosed by NGS were described in the literature, with some in case reports and others in case series or cohorts [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. In 40 out of the 319 cases (12.5%), more than 1 fungus was detected by NGS [ 26 , ...…”
Section: Laboratory Diagnosis Of Fungal Infections By Ngsmentioning
confidence: 99%
See 2 more Smart Citations